Performance of coated steel systems exposed to different media: Part I. Painted galvanized steel - del Amo, Delia Beatriz (2004)
The performance of different pre-treated galvanized steel/primer/topcoat paint systems applied on hot-dip galvanized steel sheets has been studied. Each panel was pre-treated with 5% Fe(NO3)3+15% H 3PO3 solution. After this step, the panels were coated either with acrylic (AC), alkyd (AK), vinyl (VL), epoxy base-solvent (ES) or epoxy-waterborne (EW) based corrosion-inhibiting primer using zinc molybdenum phosphate as anticorrosive pigment, and with commercially available alkyd topcoat paint. Experimental behavior of these panels under standardized salt spray chamber exposure or continuous immersion in 0.5M NaCl, 0.5M Na 2SO4 or 0.25M NaCl+0.25M Na2SO4 solutions was evaluated through periodical visual inspection (blistering and rusting degrees) and EIS measurements (corrosion evolution). Initial (dry) and final (wet) paint adhesion was also determined. EIS data has been interpreted and discussed in terms of the time dependence of the electrical (paint coating) and electrochemical (steel substrate) parameters associated with interfacial processes describing the metal/paint system deterioration. According to the electrochemical properties, visual inspection and standardized tests results, the painting systems designated as AK, ES, EW, and VL presented the best overall anticorrosive behavior under immersion conditions, but all samples failed when exposed to the salt spray chamber. System AC behaved very well in 0.25M NaCl+0.25M Na2SO4 but failed in the other media. Adhesion changes outside the tested areas showed that under immersion conditions there was lateral diffusion. Good correlation between standardized and electrochemical tests results was also obtained.